2014
DOI: 10.1016/j.algal.2014.09.007
|View full text |Cite
|
Sign up to set email alerts
|

CO2 bioremediation by microalgae in photobioreactors: Impacts of biomass and CO2 concentrations, light, and temperature

Abstract: Microalgae have the potential to recycle and bioremediate CO 2 and also produce chemical energy in the form of biomass. The potential production of renewable energy and high value products (i.e. carotenoid, antioxidants and polyunsaturated fatty acids) make large scale microalgal cultivation an attractive application. To achieve high productivity all microalgae cultures require CO 2 addition. Various microalgae species have shown different capabilities to bioremediate CO 2 . This review article reports biomass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(40 citation statements)
references
References 102 publications
0
33
0
7
Order By: Relevance
“…Light intensity controls photosynthetic growth in any microalgal system. It also affects CO 2 removal rates, biomass concentration and overall growth rate [15]. In the present study it was found that SA1 showed improvement in all the growth kinetic parameters with an increase in light intensity ( Table 1).…”
Section: Effect Of Varying Operational Parameters On Growth Kinetic Pmentioning
confidence: 77%
See 1 more Smart Citation
“…Light intensity controls photosynthetic growth in any microalgal system. It also affects CO 2 removal rates, biomass concentration and overall growth rate [15]. In the present study it was found that SA1 showed improvement in all the growth kinetic parameters with an increase in light intensity ( Table 1).…”
Section: Effect Of Varying Operational Parameters On Growth Kinetic Pmentioning
confidence: 77%
“…Conventional coal-fired power stations release roughly 7% of total emitted CO 2 into the atmosphere. In general, the flue gases emitted from the power plants consist of 10-20% CO 2 [15]. There is thus an immediate need to develop a sustainable and environment-friendly CO 2 mitigation process.…”
Section: Introductionmentioning
confidence: 99%
“…Las microalgas con metabolismo fotoautotrófico tienen ventaja sobre las de metabolismo heterotrófico y mixotrófico porque generan beneficio ambiental por fijación de CO2, además de que pueden crecer en aguas residuales y reciclar nutrientes presentes en el agua (García, 2010;Kim, 2015;Raeesossadati, Ahmadzadeh, McHenry y Moheimani, 2014;Bajpai, Ales y Zappi, 2015). Varios análisis químicos verificaron que bajo metabolismo fotoautotrófico se produce 1 kg de bio masa (compuesta entre un 40 % y 50 % de carbono) a partir de 1.5 kg a 2 kg de CO2, que entra por difusión pasiva a la célula (Mazzuca, García, Camacho, Acién y Molina, 2000).…”
Section: Resultados Cultivos Microalgales Y Consumo De Co2unclassified
“…In order to raise algae in high concentrations, it is necessary to add CO 2 to the water. By bubbling in CO 2 into the rapidly growing algal cultures, it is possible to capture the majority of CO 2 produced by the cogeneration system (for a recent review, see Raeesossadati et al 2014 and Chap. 7).…”
Section: Algae-based Wastewater Treatmentmentioning
confidence: 99%